Trend analysis of generic shifting in the Bangladesh Pharmaceutical Market (2006-2010) - Ishika, Monamee Afroze (BRAC University, 2012)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2010.